Heterologe Insemination - Aktuelle Lage und Reformbedarf aus interdisziplinärer Perspektive - Duttge, Gunnar; Engel, Wolfgang; Lipp, Volker; Zoll, Barbara (Universitätsverlag Göttingen, 2010)
The heterologous or donogenous insemination is the artificial fertilization of an ovum for reproductive purposes with the sperm of an outside donor to save the affected couples a infertility. This method is long been offered and used by the modern reproductive medicine but, however raises a number of legal, human genetic and psychological issues that are not at sufficiently resolved in the circle of experts. The present volume addresses these questions and possible answers in an interdisciplinary discussion and explores solutions. The articles go back to a workshop, which was jointly organized in cooperation of the Centre for Medical Law and the Göttingen Institute of Human Genetics. The editors hope that the recommendations resulting from this will be able to provide important impetus and support to the leaders in this field, but also to legislation and case law.